The tight-adhesion proteins TadGEF of Bradyrhizobium diazoefficiens USDA 110 are involved in cell adhesion and infectivity on soybean roots - Mongiardini, Elías Javier (2016)
Adhesion of symbiotic bacteria to host plants is an essential early step of the infection process that leads to the beneficial interaction. In the Bradyrhizobium diazoefficiens-soybean symbiosis few molecular determinants of adhesion are known. Here we identified the tight-adhesion gene products TadGEF in the open-reading frames blr3941-blr3943 of the B. diazoefficiens USDA 110 complete genomic sequence. Predicted structure of TadG indicates a transmembrane domain and two extracytosolic domains, from which the C-terminal has an integrin fold. TadE and TadF are also predicted as bearing transmembrane segments. Mutants in tadG or the small cluster tadGEF were impaired in adhesion to soybean roots, and the root infection was delayed. However, nodule histology was not compromised by the mutations, indicating that these effects were restricted to the earliest contact of the B. diazoefficiens and root surfaces. Knowledge of preinfection determinants is important for development of inoculants that are applied to soybean crops worldwide.